The Reality Of Practical Application In The Media Ba Program In The Media Faculties In Jordanian Universities Yarmouk University As A Model (Journal of Namibian Studies : History Politics Culture, 2023)
The study aimed to identify the role of the practical courses in the Faculty of Mass Communication at Yarmouk University in providing its graduates with the skills of the media labor market. The contribution of practical study courses in providing graduates with the specifications required in the labor market came to a high degree. and "Strength of Personality" with a mean of (2.58), while the contribution of the practical study courses was to provide graduates with the professional skills required in the practice of media work to a high degree, as the most important of these skills was "the ability to collect data and information from various sources easily" with a mean of (. 2.54), and "Arabic Language Proficiency" and "Accuracy and Objectivity in Media Dealing" with an arithmetic mean of (2.46) for each of them. in the digital age.